Romper com a maldição dos recursos minerais: um caminho a ser trilhado - Fernanda Alen Goncalves da Silva (2017)
The endowment of natural resources should be understood as a true "fate" in the natural law, which would provide a competitive advantage to induct the economy development. However, divine grace does not seem to be accompanied by the same presumption when the central point is economic performance. That is why natural resource rich countries tend to present levels of economic development worse than countries deprived of these riches. The observation seems at least counterproductive, and it is what the theory of the natural resource curse, object of study of this work, studies. Because of the current globalized context, the understanding of this theory can not take place in a detached form from the reality that it is imposed. In this sense, the study sought to identify the interface between the elements of the natural resource curse theory and the globalized context, in order to reveal the relationship of the international community to the supposed natural "curse" and, above all, to the underdevelopment condition of resource rich countries, such as Brazil.In unveiling the causal implication of rich countries in relation to the poverty of nations endowed with natural wealth, the study admitted the indispensability of discussing the application of the distributive justice principles, which, faced with the globalization of the new era, requires expansion into the global spectrum.Since tax policy is a prime instrument for promoting distributive justice, the study presented the goals of taxation and revealed the possibility of solving the distortions identified through the operationalization of tax policy. In this context, it has been shown that alternatives both within the internal states and within the global community need to be sought.The construction of this whole theoretical framework was necessary for the composition of a critical look at the mineral wealth of the State of Minas Gerais and the Municipality of Mariana. Therefore, the research was based on the identification of the phenomenon of the mineral resource curse in these subnational entities and on the understanding of their relation to the globalized dimension. From this approach, proposals for mineral tax policy were discussed, in view of the taxation objectives to be surveyed. Finally, the study concluded that the national perspective is essential to deal with aspects of natural resources countries curse. However, it would be naive thinking that, in view of the connection with the globalized reality, only the intra-territorial measures would suffice. Breaking with the mineral curse requires going further, requires facing the globalized reality, and therefore requires approaching global alternatives.